An economical optimization model for deteriorating system integrated with statistical process control and condition-based maintenance. Issue Volume 32:Issues 3(2020) (2nd July 2020) - Zhang, Cong; Zhu, Haiping; Wu, Jun; Ma, Leibo; Cheng, Jiaxin; Wang, Hui
Abstract: The purpose of this article is to balance product quality requirements and maintenance costs. Considering that manufacturing system is deteriorating and its maintenance situations are complex, maintenance strategies, control chart parameters, and sampling rules are designed for different stages of the system life cycle. A searching algorithm combined particle swarm optimization with heuristic rules is introduced to solve this integrated optimization problem. A numerical example study is implemented to validate the effectiveness and rationality. A comparison model is built to illustrate the advantages of the proposed model. Sensitivity analysis is also performed to investigate the effect of nine cost factors.